Financial Statement Complexity and Meeting Analysts’ Expectations - Filzen, Joshua J.; Peterson, Kyle (Contemporary Accounting Research, 2015)
Abstract We examine whether firms with greater financial statement complexity are more likely to meet or beat analysts’ earnings expectations. We proxy for financial statement complexity using the firm's industry and year adjusted accounting policy disclosure length. Firms with more complex financial statements are more likely to just beat expectations than just miss expectations. Firms with complex financial statements appear to use expectations management to beat expectations, but do not use earnings management. Corroborating these findings, we find analysts rely more on management guidance for more complex firms. Firms with complex financial statements are also more likely to have analysts exclude items from actual “street earnings,” but tests suggest this strategy is not specifically used by complex firms to beat expectations. The effect we document is specific to analyst forecasts and not to other alternative benchmarks.